MELASMA NA GESTAÇÃO: REVISÃO INTEGRATIVA PARA PREVENÇÃO E PROTOCOLO CLÍNICO DE ATENDIMENTO - Rodrigues, Tanise Schorn (2020)
Introduction: During pregnancy, many physiological adaptations occur in the female organism, many of them cause discomfort and still others may be permanent. Due to hormonal changes in some women, melasmas become more apparent, causing discomfort to their self-esteem and well-being. Objective: To create a clinical protocol for the care of pregnant women with melasma to be used in the context of primary health care. Methodology: An integrative review was carried out with searches in the Lilacs, Medline, Ibecs and PubMed databases, with no time record. Subsequently, searches were carried out in databases and books in the area. A compilation of the data was made and the protocol was built with flowcharts, images and tables so that it was practical and easy to understand. Results: The first stage was carried out with searches in the literature in order to analyze how care is being carried out to minimize the permanence of post-pregnancy melasma. In this process it was observed that melanosis and its prevention factors need to be addressed during the gestational period, since the appearance of this hyperpigmentation considerably affects the quality of life of women, which can cause the appearance of several negative feelings to self-esteem and image of the woman. In this direction, the construction of the protocol aimed to build an instrument where all professionals who perform prenatal care are able to identify and mainly treat, with low-cost products and easy access to women. Final Considerations: The creation of the protocol aims to contribute to the practice of professionals and assist in the organization of the team's work process, and corroborates the process of care and treatment, improving the quality of life of women. The professionals' adherence to this instrument will enable specialized and singular attention to women's health, positively interfering in the prognosis of gestational melasmas. Product and its applicability: The research process resulted in the creation of a clinical protocol for the care of pregnant women with melasma in primary health care. Its applicability is aimed at health professionals and academics, with an emphasis on the identification and treatment of melasma. The final version of the protocol is available digitally.